Changes in physicochemical parameters of duck eggs and extra-embryonic structures during incubation - Jakub Biesek; Sebastian Wlaźlak; Marek Adamski (Animal, 2023)
Duckling embryogenesis should be deepened due to the hatching technology and its modification possibilities. Many changes occur in incubated eggs, which expose the embryo to hazards. The study aimed to analyse the physicochemical properties of eggshell, yolk, thick albumen (TA), and amniotic fluid (AF) of incubated hatching eggs from 52-week-old Cherry Valley ducks. The morphological features of 18 fresh eggs were analysed. Over 28 days, a total of 800 eggs underwent incubation. Eggshell surface temperature and egg weight loss were measured on days 1, 4, 7, 10, 14, 18, 21, and 25. Eggshell, TA, AF, and yolk were collected from eggs at incubation days 1–21 (every week). TA was collected on days 0, 1, and 7, while AF on days 7, 14, and 21. The analysis covered a range of physicochemical parameters. Eggshell thickness decreased with incubation, reaching its lowest point posthatch (P < 0.001). The highest pH for TA was recorded on day 1, while the lowest was on day 7 when comparing days 0, 1, and 7 (P < 0.001). TA pH was consistently higher than in AF (P < 0.001). However, the pH of TA was the highest on day 1 and the lowest on day 7 (P < 0.001). Yolk pH increased from days 1 to 21 (P < 0.001). There was also a noticeable in egg weight loss (0.34% daily) (P < 0.001). Vitelline membrane strength decreased from day 0 to day 1 (P < 0.001). Lysozyme activity in thick albumen on day 7 was higher than on days 0 and 1 (P < 0.001). Lysozyme activity in AF was higher on day 21 than days 7 and 14 (P < 0.001). TA viscosity was highest on day 0 and lowest on day 1, compared to other days (P < 0.001). AF viscosity and CP content exhibited an increase on day 21 as compared to days 7 and 14 (P < 0.001). The CP content in TA was notably higher on day 7 than on days 0 and 1 (P < 0.001). Polyunsaturated fatty acids declined, while monounsaturated and transfatty acids increased (P < 0.001). Viscosity and lysozyme activity increased on day 7 in TA and day 21 in AF. TA and the amniotic cavity appeared to facilitate the transfer of substances, particularly CP. Viscosity could be an indicator for optimising incubation conditions, as incorrect changes can affect embryo mortality. The results showed the different utilisation of nutrients, such as fatty acids. It could support research on the in-ovo administration of various substances.